2014
DOI: 10.3762/bjoc.10.77
|View full text |Cite
|
Sign up to set email alerts
|

Towards allosteric receptors – synthesis of β-cyclodextrin-functionalised 2,2’-bipyridines and their metal complexes

Abstract: SummaryHerein, we present three new 2,2’-bipyridines that carry two β-cyclodextrin moieties in different substitution patterns. When coordinated by zinc(II) or copper(I) ions (or their complexes), these compounds undergo conformational changes and switch between “open” and “closed” forms and thereby bringing together or separating the cyclodextrin moieties from each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc(II) triflate [Zn(OTf) 2 ] and iron(II) perchlorate [Fe(ClO 4 ) 2 ] were chosen as suitable metal sources for the dynamic complexes, owing to their favorable solubility properties in methanol. Two different ligands were in addition chosen: 5,5′‐ and 4,4′‐substituted 2,2′‐bipyridines, expected to display relatively minor structural differences of the different complexes compared to the 3,3′‐ or 6,6′‐substituted counterparts . Crystal structures have been reported for some of the homoleptic complexes .…”
Section: Resultsmentioning
confidence: 99%
“…Two different ligands were in addition chosen: 5,5′-and 4,4′-substituted 2,2′-bipyridines, expected to display relatively minor structural differences of the different complexes compared to the 3,3′-or 6,6′-substituted counterparts. [35][36][37][38] Crystal structures have been reported for some of the homoleptic complexes. [39][40][41][42][43][44][45][46][47][48] For detection purposes, 5,5′-dimethyl-2,2′-bipyridine L1 and stable, isotope-labeled ligand [D 6 ]-4,4′-dimethyl-2,2′-bipyridine L2, prepared using microwave-assisted deuteration, [49] were thus used to construct the complexes (Figure 1).…”
Section: Initial Investigation Of Homoleptic Complexesmentioning
confidence: 99%
“…In a second approach, we utilized β‐cyclodextrins due to their known ability to bind a great variety of nonpolar substrates7 and their tunable solubility, which we connected to the bipyridines by thiourea moieties 8. Herein, we report the new, water‐soluble derivative 1 of these systems and its allosterically controlled binding behavior towards capsaicin.…”
Section: Methodsmentioning
confidence: 99%